Syringin as a novel therapeutic agent for renal cell carcinoma by targeting EGFR/PI3K/Akt pathway and enhancing sunitinib efficacy - Zixuan Chen; Sheng Cheng; An Xu; Chengtao Han; Xing Jia; Min Liu (Journal of Functional Foods)
Syringin, a natural bioactive compound extracted from Acanthopanax senticosus, has demonstrated potential therapeutic value in cancer treatment. However, its efficacy in treating renal cell carcinoma (RCC) remains unexplored. This study aims to investigate the therapeutic effects and underlying mechanisms of Syringin in RCC. In this study, network pharmacology, molecular docking validation, and bioinformatics were employed to predict the mechanisms by which Syringin affects RCC. In vitro experiments showed that Syringin inhibited RCC cell viability and reduced the IC50 of Sunitinib, enhancing its therapeutic effect. Syringin also inhibited RCC cell proliferation and migration and promoted apoptosis. The combination of Syringin and Sunitinib demonstrated an enhanced inhibitory effect. Western blot analysis confirmed that Syringin’s anti-RCC effects are mediated through the EGFR/PI3K/Akt pathway. In conclusion, our findings indicate that Syringin exhibits inhibitory effects on RCC cells and enhances their sensitivity to Sunitinib, offering a novel approach to exploring treatment strategies for Sunitinib-resistant RCC.